Hypohidrotic Ectodermal Dysplasia: a rare inherited multisystem disorder (Indian Journal of Experimental Biology (IJEB), 2021)
Hypohidrotic ectodermal dysplasia (HED), also known as Christ-Siemens-Touraine syndrome, is a rare X-linked genetic disorder characterized by the faulty development of the ectodermal structures, resulting in most notably anhydrosis/ hypohidrosis, hypotrichosis and hypodontia. Here, we report clinical presentation of a HED case. A female child aged 8 years was brought with complaints of high grade fever along with upper respiratory tract illness symptoms. She also had recurrent episodes of unexplained hyperpyrexia and thirst. Physical examination revealed characteristic appearance which aided in arriving at a diagnosis. Diagnosing this disorder in early life prevents mortality which is high especially during neonatal period. Therefore, it is essential for the treating clinician to have basic knowledge on the clinical presentations as well as complications of this specific genetic disease so that it is not missed. It is rare to see a classical case of hypohidrotic ectodermal dysplasia in female children with typical phenotypic features hence, this case report is presented.